Cultural norms and corporate fraud: Evidence from the Volkswagen scandal - Iftekhar Hasan; Felix Noth; Lena Tonzer (Halle Institute for Economic Research (IWH), 2020)
We investigate whether cultural norms shaped by religion drive consumer decisions after a corporate scandal. We exploit the notice of violation by the US Environmental Protection Agency in September 2015 accusing Volkswagen (VW) of using software to manipulate car emission values during test phases. We show that new registrations of VW cars decline significantly in German counties with a high share of Protestants following the VW scandal. Our findings document that the enforcement culture in Protestantism facilitates penalising corporate fraud. We corroborate this channel with a survey documenting that Protestants respond significantly different to fraud but not to environmental issues.
Keywords: D12; O30; Q50; Z12; 330; religion; corporate scandal; consumer choice; climate change